Josiah Gould, A Digest of the Statutes of Arkansas Embracing All Laws of a General and Permanent Character in Force the Close of the Session of the General Assembly of 1856 380 381 - 82 (1837) - (:unkn) unknown (General Publisher, 1837)
Prohibited the concealed carrying of any pistol, dirk, butcher or large knife, sword cane, unless “upon a journey.”
--
Keywords: CARRY - CONCEALED